Logging and Log Interpretation - The Borehole Televiewer – A New Logging Concept for Fracture Location and Other Types of Borehole Inspection - J. Zemanek; R. L. Caldwell; E. E. Glenn; S. V. Holcomb; L. J. Norton; A. J. D. Straus (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1970)
A new and unique logging tool, called the Borehole Televiewer (BHTV), has been developed to inspect boreholes and to evaluate formations. Even though geologists and engineers have had only about 3 years' experience with the BHTV, the thinking of many of them has been radically influenced by the fascinating and revealing "log-picture" recorded with the tool. The BHTV fills a need for a logging tool that can produce a direct and descriptive record of the physical properties of the borehole environment. Although primarily developed to evaluate fractured reservoirs, the BHTV has been used successfully to solve a variety of problems related to formation evaluation and borehole inspection. Geologists and petroleum engineers have been confounded for many years by the problems of locating and evaluating fractures. Interpretation of the usual resistivity, acoustic or radioactivity logs, as well as the analysis of cores, for evaluation of fractured reservoirs is extremely difficult and often not definitive. This is understandable since analysis of cores from fractured formations has reported variously: (a) low porosity, (b) no effective permeability, (c) lack of any matrix oil saturation and (d) oil stains on fracture planes as the only indications of potential production.14 In recent years acoustic amplitude logs have been introduced and used with varying degrees of success to locate fractures.8'9'11"13 Conventional amplitude logs at best give only qualitative answers where quantitative ones are desired. The logs reveal nothing of the orientation of the fractures. In addition to these logs, various types of cameras, television, and rubber impression packers have been used for borehole inspection. (See Appendix.) The BHTV logging tool supplies both the quantitative and the orientation answers about fractures. The borehole can be filled with any homogeneous, gas-free liquid such as fresh water, saturated brine, crude oil or drilling muds. This tool takes an "acoustic picture" of the borehole wall. The resulting log is a representation of the borehole wall as if it were split vertically and laid flat. The log is oriented with respect to magnetic north. Any physical changes in the borehole wall are seen as changes in picture intensity. In this way, fractures, deformation or pits are reflected on the log. Tool Description The fundamental parts of the BHTV are shown in Fig. 1. A piezoelectric transducer probes the borehole wall with bursts of acoustic energy. A flux-gate magnetometer senses the earth's magnetic field and provides the means for determining the orientation of the log. A motor rotates the transducer and mag-